2016
DOI: 10.1080/2162402x.2016.1150399
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antineoplastic treatment is associated with the use of antibiotics that modulate intestinal microbiota

Abstract: Reduced anticancer efficacy of cyclophosphamide and platinum salts has been reported in animals treated with anti-Gram-positive antibiotics. These effects were related to translocation of Gram-positive bacteria during mucositis with subsequent induction of cytotoxic oxygen reactive species and tumor invasion by pathogenic Th17 cells. To assess these hypotheses in a clinical setting, we identified patients receiving cyclophosphamide for chronic lymphocytic leukemia (CLL) and cisplatin for relapsed lymphoma. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 15 publications
1
67
0
3
Order By: Relevance
“…An additional study found that patients receiving cyclophosphamide for chronic lymphocytic leukaemia who received antimicrobials with a Gram‐positive spectrum had significantly reduced progression free and overall survival times compared to those receiving primarily Gram‐negative spectrum antimicrobials or no antimicrobials at all. This finding is suspected to be related to alterations in the microbiome as discussed above …”
Section: Choice Of Antimicrobialmentioning
confidence: 90%
“…An additional study found that patients receiving cyclophosphamide for chronic lymphocytic leukaemia who received antimicrobials with a Gram‐positive spectrum had significantly reduced progression free and overall survival times compared to those receiving primarily Gram‐negative spectrum antimicrobials or no antimicrobials at all. This finding is suspected to be related to alterations in the microbiome as discussed above …”
Section: Choice Of Antimicrobialmentioning
confidence: 90%
“…Likewise, Viaud et al observed that receipt of antibiotics with activity against Gram-positive bacteria reduced T-helper lymphocyte and lymphoma responses in mice treated with cyclophosphamide [17]. Beyond animal models, recently it was shown that patients being treated with cyclophosphamide for chronic lymphocytic leukemia and cisplatin for relapsed lymphoma who also received anti-Gram-positive antibiotics had significantly lower overall response rate and survival [18]. …”
Section: How Antibiotic-induced Microbiome Alteration Affects the Canmentioning
confidence: 99%
“…В клинических исследованиях при лечении больных хроническим лимфолейкозом (исследование CLL8, схемы FCR и FC; n = 800) и рецидивирующими КЛИНИЧЕСКАЯ ОНКОГЕМАТОЛОГИЯ лимфомами (схемы с цисплатином, n = 122) также было показано негативное влияние антибиотиков против грамположительных бактерий на противоопу-холевый эффект циклофосфамида и цисплатина [59]. У пациентов, получавших анти-грамположительные антибиотики, отмечено ухудшение общего ответа (42,9 vs 70,3 %; p = 0,016), снижение медианы выжи-ваемости без прогрессирования (ВБП; 2,3 vs 11,5 мес.…”
Section: профилактика нарушений микробиотыunclassified